Changes in symptom intensity and emotion valence during the process of assimilation of a problematic experience: A quantitative study of a good outcome case of cognitive-behavioral therapy. (4th July 2017) - Basto, Isabel; Pinheiro, Patrícia; Stiles, William B.; Rijo, Daniel; Salgado, João
Abstract: The assimilation model describes the change process in psychotherapy. In this study we analyzed the relation of assimilation with changes in symptom intensity, measured session by session, and changes in emotional valence, measured for each emotional episode, in the case of a 33-year-old woman treated for depression with cognitive-behavioral therapy. Results showed the theoretically expected negative relation between assimilation of the client's main concerns and symptom intensity, and the relation between assimilation levels and emotional valence corresponded closely to the assimilation model's theoretical feelings curve. The results show how emotions work as markers of the client's current assimilation level, which could help the therapist adjust the intervention, moment by moment, to the client's needs.